O03.4 The role of social science and public patient involvement in the development of novel rapid diagnostic tests for stis and antimicrobial resistance detection. (8th July 2017) - Pacho, Agata; Broad, Claire; Harding-Esch, Emma; Sadiq, Syed Tariq; Fuller, Sebastian S
Abstract : Introduction: Patient and Public Involvement (PPI) is increasingly seen as necessary for conduct of high-impact ethical research, but when focused on short-term treatable sexually transmitted infections (STIs) it can be challenging to gain participants. The Precise Study is a collaboration to develop and evaluate point of care tests (POCTs) for short-term STI infection and Antimicrobial Resistance (AMR) detection. We explored patient opinions concurrent to POCT development, through qualitative interviews and PPI activities. Methods: Qualitative 1-on-1 interviews were conducted with a purposive sample of patients in three sexual health clinics (SHCs) in England. PPI activities included development of a patient and public advisory group (PAG). Interview topics were presented for discussion at one PAG meeting. Members were unaware of qualitative interview results until after they gave their opinions. Findings from qualitative interviews were compared with PAG meeting notes to better understand results of the two approaches. Results: 31 patient interviews were conducted in SHCs: 11 women, 12 heterosexual men and 8 men who have sex with men. Most patients felt POCTs were preferable to standard care, and many suggested ways to implement the tests in new clinical pathways. Our PAG had 4 members of the public: 3 women and 1 man, all with previous experience in healthcare settings. PAG member opinions of the POCTs and importance of the AMR test mirrored key themes found in patient interviews, however, PAG members focused on the potential for advocacy that POCTs provide, and suggested publicising rapid turnaround of results to encourage testing in high-risk groups with low clinic attendance. Conclusion: We have demonstrated that PPI is possible for stigmatised, treatable short-term STIs, provides new insights into care and utility and allows for continued dialogue on implementing solutions to meet patient concerns. We suggest that where possible, qualitative research is used to iterate the diversity of patient opinions, and is complemented by PPI to build patient-centred solutions.